Comparison of three-year oncological results after restorative low anterior resection, non-restorative low anterior resection and abdominoperineal resection for rectal cancer. Issue 4 (April 2023) - Hol, Jeroen C.; Burghgraef, Thijs A.; Rutgers, Marieke L.W.; Crolla, Rogier M.P.H.; van Geloven, Nanette A.W.; Leijtens, Jeroen W.A.; Polat, Fatih; Pronk, Apollo; Smits, Anke B.; Tuynman, Jurriaan B.; Verdaasdonk, Emiel G.G.; Consten, Esther C.J.; et al.
Abstract: Introduction: Oncological outcome might be influenced by the type of resection in total mesorectal excision (TME) for rectal cancer. The aim was to see if non-restorative LAR would have worse oncological outcome. A comparison was made between non-restorative low anterior resection (NRLAR), restorative low anterior resection (RLAR) and abdominoperineal resection (APR). Materials and methods: This retrospective cohort included data from patients undergoing TME for rectal cancer between 2015 and 2017 in eleven Dutch hospitals. A comparison was made for each different type of procedure (APR, NRLAR or RLAR). Primary outcome was 3-year overall survival (OS). Secondary outcomes included 3-year disease-free survival (DFS) and 3-year local recurrence (LR) rate. Results: Of 998 patients 363 underwent APR, 132 NRLAR and 503 RLAR. Three-year OS was worse after NRLAR (78.2%) compared to APR (86.3%) and RLAR (92.2%, p < 0.001). This was confirmed in a multivariable Cox regression analysis (HR 1.85 (1.07, 3.19), p = 0.03). The 3-year DFS was also worse after NRLAR (60.3%), compared to APR (70.5%) and RLAR (80.1%, p < 0.001), HR 2.05 (1.42, 2.97), p < 0.001. The LR rate was 14.6% after NRLAR, 5.2% after APR and 4.8% after RLAR (p = 0.005), HR 3.22 (1.61, 6.47), p < 0.001. Conclusion: NRLAR might be associated with worse 3-year OS, DFS and LR rate compared to RLAR and APR.